The Bad guys. 4, Attack of the zittens - Blabey, Aaron (New York, NY : Scholastic Inc., 2017)
"It's a zombie kitten apocalypse! Can the Bad Guys save the world from evil Dr. Marmalade's meowing monsters?!? They'll need help from foxy Agent Fox, a swampy secret zombie antidote, and the feistiest, toothiest, hungriest granny around. Get ready to watch the fur fly!"--Page 4 of cover.
"First published by Scholastic Australia Pty Limited in 2016."